Anti-TNFα alters the natural history of experimental Crohn's disease in rats when begun early, but not late, in disease - Schmiedlin-Ren, Phyllissa (Am J Physiol Gastrointest Liver Physiol, 2016)
Anti-TNFα therapy decreases inflammation in Crohn's disease (CD). However, its ability to decrease fibrosis and alter the natural history of CD is not established. Anti-TNF-α prevents inflammation and fibrosis in the peptidoglycan-polysaccharide (PG-PS) model of CD. Here we studied anti-TNF-α in a treatment paradigm. PG-PS or human serum albumin (HSA; control) was injected into bowel wall of anesthetized Lewis rats at laparotomy. Mouse anti-mouse TNF-α or vehicle treatment was begun day (d)1, d7, or d14 postlaparotomy. Rats were euthanized d21-23. Gross abdominal and histologic findings were scored. Cecal levels of relevant mRNAs were measured by quantitative real-time PCR. There was a stepwise loss of responsiveness when anti-TNFα was begun on d7 and d14 compared with d1 that was seen in the percent decrease in the median gross abdominal score and histologic inflammation score in PG-PS-injected rats [as %decrease; gross abdominal score: d1 = 75% (P = 0.003), d7 = 57% (P = 0.18), d14 = no change (P = 0.99); histologic inflammation: d1 = 57% (P = 0.006), d7 = 50% (P = 0.019), d14 = no change (P = 0.99)]. This was also reflected in changes in IL-1β, IL-6, TNF-α, IGF-I, TGF-β1, procollagen I, and procollagen III mRNAs that were decreased or trended downward in PG-PS-injected animals given anti-TNF-α beginning d1 or d7 compared with vehicle-treated rats; there was no effect if anti-TNF-α was begun d14. This change in responsiveness to anti-TNFα therapy was coincident with a major shift in the cytokine milieu observed on d14 in the PG-PS injected rats (vehicle treated). Our data are consistent with the clinical observation that improved outcomes occur when anti-TNF-α therapy is initiated early in the course of CD.